Zinc Improves Functional Recovery by Regulating the Secretion of Granulocyte Colony Stimulating Factor From Microglia/Macrophages After Spinal Cord Injury - Li, Xian; Chen, Shurui; Mao, Liang; Li, Daoyong; Xu, Chang; Tian, He; Mei, Xifan (Frontiers in Molecular Neuroscience, 2019)
Zinc promotes motor function recovery after spinal cord injury (SCI), however the mechanisms of zinc is not fully understood. Our study aimed to elucidate the effects of zinc on neuronal recovery and the mechanism by granulocyte colony stimulating factor (G-CSF) after SCI. SCI model was established by Allen's method. The injured animals were given glucose and zinc gluconate (ZnG) (30mg/kg) for the first time at 2 h after injury for 3 days. Cytokines antibody array ware used for screening the inflammation changing of SCI lesion. Immunofluorescence was used for cytokines derivation. And then cell isolation by magnetic beads of SCI lesion. Effect of Zinc on apoptosis after SCI by TUNEL staining and Western Blot. Basso mouse scale (BMS) scores and immunofluorescence were employed for neuron apoptosis and functional recovery. We found that zinc administration significantly increased the expression of 19 cytokines in SCI lesion, among them, G-CSF is the most elevated cytokines which was secreting by microglia/macrophages (M/Ms) through Nuclear factor-kappa B (NF-κB) signaling pathway after SCI. As a matter of fact, the increased G-CSF of SCI lesion induced neuronal apoptosis decreased after SCI in inflammation milieu by decreased cleaved- caspase 3 expression in neuron, which promote the functional recovery. These results indicated that zinc increase the expresion of G-CSF secreted by M/Ms, which leads to decreased neuronal apoptosis after SCI.